Ad hoc networks : 6th International ICST Conference, ADHOCNETS 2014, Rhodes, Greece, August 18-19, 2014 : revised selected papers - Mitton, Natalie; Gallais, Antoine Hedley 1980-; Erol-Kantarci, Melike; Papavassiliou, Symeon; International Conference on Ad Hoc Networks 2014 : Rodas, Grecia) (Cham : Springer, 2014)
This book constitutes the thoroughly refereed proceedings of the 6th International Conference on Ad Hoc Networks, ADHOCNETS 2014, held in Rhodes, Greece, in August 2014. The 16 regular and invited papers presented were carefully selected and reviewed from numerous submissions and cover a wide range of applications, such as mobile ad hoc networks, sensor networks, vehicular networks, intelligent transportation systems, wireless sensor networks security.
Keywords: REDES AD HOC (REDES DE COMPUTADORAS) -- CONGRESOS; REDES DE COMPUTADORAS -- CONGRESOS